ENGINEERING OF ABSORPTION COLUMN AND THE ADSORBENT FROM FERRO POWDER WASTE FOR PURIFICATION THE BIOGAS FROM PALM OIL MILL EFFLUENT - siti masriani rambe; Edwin Harianto Sipahutar (Jurnal Dinamika Penelitian Industri, 2017)
AbstractIt was conducted to engineering the adsorption column by using ferro powder waste as adsorbent to removal the H2S content of biogas from Palm Oil Mill Effluent. The first step it was conducted to calculated the adsorption column as purification column by character Palm Oil Mill Effluent (POME) considering. Further, is was conducted to annealed the ferro powder from industrial waste workshop in north Sumatera. Thus, it was conducted to annealed with temperature variation (800°C, 900°C and 1000°C) and the thick adsorbent (1 cm, 2 cm).The  result shows that  each adsorbent product is tested by applied of using direct that  puts in the  adsorbent  column. Applied research is conducted by flowing biogas trought column that the adsorbent is alreadyin the column. Temperature condition and the width of adsorbent was effecting of adsorption the H2S biogas and the optimal condition are 1000°C temperature and 2 cm of width adsorbance